Keefektifan Pembenah Tanah, Pemupukan, dan Mikoriza untuk Pertumbuhan Tanaman Karet di Lahan Bekas Tambang Timah - Rusli Rusli; Yulius Ferry; Bariot Hafif; Edi Wardiana (Jurnal Tanaman Industri dan Penyegar, 2016)
The use of post tin mining land for agricultural purpose is constrained by the coarse soil texture (sand), low C-organic, acid pH and low nutrient content which can be rehabilitated with soil ameliorant treatment. The research objective was to determine the best soil management of post tin mining land through the use of soil ameliorant, fertilizer, and mycorrhiza application for rubber plant growth. The research was conducted in Mandor District, Landak Regency, West Kalimantan, from 2014 until 2015. The experiment design was a split plots with 3 replications. The main plot was the use of ameliorant i.e M1 (16 kg of compost + 24 kg of quartz tailings), M2 (16 kg of clay soil + 24 kg of quartz tailings),  M3 (8 kg of compost + 8 kg of clay soil + 24 kg of quartz tailings), and control (without soil ameliorant). Subplot was fertilizer dosage i.e D1 (100% of the recommended doses), D2 (100% of the recommended doses + 100 g of mycorrhiza), D3 (125% of the recommended doses), D4 (125% of the recommended doses + 100 g of mycorrhiza). The study was conducted at altitude of  50 m asl, type A climate, annual rainfall at 2.600 mm, sandy soil (82.2%) with very low N (0.09%), very low K (0.08 cmol (+)/kg), and low P (9.24 ppm). Variables observed were the rubber plant growth (plant height, stem diameter, and number of leaves). Result showed that optimizing the rubber growth at post tin mining land needs soil ameliorants application such as compost and clay. Meanwhile, the optimal dose of fertilizer is 125% of the recommended dose plus 100 g of mycorrhiza.